An inguinal hernia that arose after robot‐assisted radical prostatectomy and the repair of an intraoperative external iliac vein injury: A case report. Issue 4 (22nd February 2021) - Nakanishi, Ryo; Igarashi, Kazuharu; Hosaka, Miki; Ishi, Satoru; Tsutsui, Atsuko; Wakabayashi, Go
Abstract: This case involved a 63‐year‐old man. He underwent robot‐assisted radical prostatectomy (RARP) for prostate cancer. One year after the operation, he consulted our hospital about left inguinal swelling. Under a diagnosis of a left external inguinal hernia, transabdominal preperitoneal repair (TAPP) was performed under general anesthesia. The inside of the hernia orifice had been damaged by the RARP, and the resultant fibrosis was so marked that it was difficult to dissect the preperitoneal space. Furthermore, an external iliac vein injury occurred during the operation. The bleeding was controlled, and we used laparoscopic continuous non‐absorbable sutures to repair the external iliac vein injury. The number of TAPP procedures performed after radical prostatectomy has been increasing in recent years, but dissecting the preperitoneal space inside a hernia orifice is difficult. Although external iliac vein injuries are rare complications of TAPP procedures, they can be laparoscopically repaired.